CALCINOSIS CUTIS PROBABLY CAUSED BY SULPYRINE - OHTAKA, Kou (Japanese Journal of National Medical Services, 1992)
We found 6 cases of calcinosis cutis, which is assumed to be caused by large intravenous dosis of sulpyrine injected against the pain of Hansen disease. There were 2 male and 4 female cases. Their age ranged from 56 to 86. The types of disease were as follows: 5 L-type and 1 T-type. The periods, in which the longer large dose injection therapy was applied, were mainly distributed from 1954 to 1977; in the case 1, 4, 940 injections were carried out mainly at the lateral sides of both upper arms for last 10 years and we found the calcinosis on the same site. Table 1 shows the names of pains at that time, the site of calcinosis, serum Ca, P, Al-F, urea nitrogen and anti-PGL antibody ; no titers corresponding to the possible metabolic abnormality were observed in any case. Besides, the pathoThistological findings by H. E. staining, the differential thermal and gravitational analyses of extirpated calcium component, the identification of crystalline compounds by X-ray diffraction patterns, and the quantification of F, P and Ca by chemical analysis were performed, and thus we here report their results.